1994
DOI: 10.1093/brain/117.2.235
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of oligodendroglial inclusions in multiple system atrophy and its relevance to clinical symptomatology

Abstract: In this study a semiquantitative mapping of oligodendroglial cytoplasmic inclusions (GCIs), a feature of oligodendroglial degeneration in multiple system atrophy (MSA), was undertaken by means of a sensitive silver technique in 14 brains and 11 spinal cords of patients with various combinations of striatonigral degeneration, olivopontocerebellar atrophy and autonomic failure. The results show a system-bound extensive degeneration of interfascicular, perineuronal and perivascular oligodendrocytes. Oligodendrogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
238
2
8

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(256 citation statements)
references
References 0 publications
8
238
2
8
Order By: Relevance
“…Although cognitive dysfunction represents an exclusion criterion in the diagnosis of MSA, several studies reported frontal lobe-associated cognitive dysfunction in patients with MSA, by means of comprehensive neuropsychological testing [26,27]. Pathological studies evaluating neuronal morphology in detail and distribution of GCIs have provided evidence of cortical involvement especially in the frontal cortex and its associated white matter as well as in the striatum of patients with MSA, suggesting that GCIs in these areas may contribute to cognitive deficits [15,24]. Recent longitudinal and voxel-based MRI studies additionally supported the notion of cortical involvement in patients with MSA, demonstrating widespread cortical atrophy of the frontal, parietal, and insular areas [3,14,21].…”
Section: Discussionmentioning
confidence: 99%
“…Although cognitive dysfunction represents an exclusion criterion in the diagnosis of MSA, several studies reported frontal lobe-associated cognitive dysfunction in patients with MSA, by means of comprehensive neuropsychological testing [26,27]. Pathological studies evaluating neuronal morphology in detail and distribution of GCIs have provided evidence of cortical involvement especially in the frontal cortex and its associated white matter as well as in the striatum of patients with MSA, suggesting that GCIs in these areas may contribute to cognitive deficits [15,24]. Recent longitudinal and voxel-based MRI studies additionally supported the notion of cortical involvement in patients with MSA, demonstrating widespread cortical atrophy of the frontal, parietal, and insular areas [3,14,21].…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease dementia (PDD), dementia with Lewy bodies (DLB), and multiple system atrophy (MSA) are characterized by the formation of cellular inclusions containing pathological forms of the pre-synaptic protein α-synuclein. These pathologies include Lewy bodies (LB), Lewy neurites (LN), and Lewy grains (LG) in PDD and DLB [33] and glial cytoplasmic inclusions (GCI) in MSA [31]. α-Synuclein is a small molecular weight protein which regulates the functioning of dopamine transporter and tyrosine hydroxylase [27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a fundamental cytoskeletal alteration of oligodendrocytes occurs in MSA [18,50,170] resulting in the formation of characteristic 'glial cytoplasmic inclusions' (GCI) [135] which can be observed in the substantia nigra, striatum, inferior olivary nucleus, pontine nuclei, and cerebellum [105]. A close association between GCI and microtubules has also been demonstrated [129], aberrant or ectopic expression of cdk5 and MAPK leading to abnormal phosphorylation of microtubule cytoskeletal proteins and the formation of inclusions.…”
Section: Cellsmentioning
confidence: 99%